Labour market regulations and high quality employment in EU-15 countries. Issue 3 (3rd July 2018) - Bilbao-Ubillos, Javier; Alsasua, Jesús-Luis; Intxaurburu, Gurutze; Ullibarri-Arce, Miren
Abstract : The elements that we usually include under the concept of "labour market institutions" exert a clear influence on the workings of the labour market. However, the assessment of labour market policies and institutions remains mostly focused on their impact on the quantity of jobs, while people's well-being depends crucially on how good their jobs are. This paper is a modest attempt to contribute some evidence and insight to the debate on the effects that particular institutional configurations have on the generation of high-quality employment.